Sandwich-like nanocomposite electrospun silk fibroin membrane to promote osteogenesis and antibacterial activities. (March 2022) - Xiang, Jing; Li, Yuzhou; Ren, Mingxing; He, Ping; Liu, Fengyi; Jing, Zheng; Li, Yong; Zhang, He; Ji, Ping; Yang, Sheng
Highlights: A novel nanocomposite multifunctionalized sandwich-like GBR membrane (SGM) was designed for GBR. The inner layer of the SGM integrated with nHA promoted osteoblast differentiation and mineralization. The surface layer of the SGM integrated with nZnO displayed antibacterial properties. SGM simultaneously exhibited enhanced osteogenic properties and antimicrobial activities in vitro and in vivo . Abstract: Barrier membranes have broad application prospects in guided bone regeneration (GBR), but their use in orthopedic and dental applications is severely limited by the germ-laden microenvironment and soft-hard tissue hierarchy. Thus, a novel nanocomposite multifunctionalized sandwich-like GBR membrane (SGM) with enhanced osteogenic properties and antimicrobial activities was fabricated by the sequential electrospinning of zinc oxide nanoparticle-doped silk fibroin (nZnO/SF), pure SF, and hydroxyapatite nanoparticle-doped SF (nHA/SF). SEM images demonstrated a well-developed porous three-dimensional sandwich-like hierarchical structure, while TEM, FTIR, XRD and EDX analyses confirmed that nZnO and nHA were successfully incorporated into the SF nanofibers. The water contact angle test indicated that the SGM exhibited satisfactory hydrophilicity after integration with nZnO and nHA. In vitro biological experiments proved that SGM had good cytocompatibility with MC3T3-E1 and L929 cells and promoted the differentiation and mineralization of MC3T3-E1 cells. Additionally, antibacterial assays suggested that the SGM exhibited noticeable antimicrobial activity in vitro and in vivo . Furthermore, the SGM promoted bone formation in both rat calvarial defect models and periodontal defect models. Consequently, the multifunctionalized nanofibrous SGM, which simultaneously exhibits good biocompatibility and enhanced osteogenic and antimicrobial properties, holds promise for GBR applications.